SPIRITUALITAS URBAN DALAM PENCIPTAAN KARYA SENI RUPA KONTEMPOTER - Gede Jaya Putra (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2019)
This article discusses the rate of growth from traditional to postmodernism visualized through the work of contemporary art. Based on observations in the field with the Kerobokan village as an observation location whose growth has been categorized as urban. The work focuses on the periodization of change by looking for new meanings that can be used as a process of awareness of current cultural values. Sources of data obtained through a qualitative approach using descriptive analysis method with interview techniques in 2015. Creation uses the theory of Alma M. Hawkins namely exploration, improvisation, and forming. Along with the Faucault Knowledge and Power Relations theory to read the discourse and cultural phenomena under study. Employment shows the results of the life cycle of the postmodernism period, the development of the stage of life is so fast as if there is no pause in accordance with the results of research on the kerobokan community. Likewise on cultural values, significant changes are present through the procession of postmodern marriage, which currently not only questions spirituality / religiosity but gives birth to a new discourse on wedding fashion.